RhIr@MoS2 nanohybrids based disposable microsensor for the point-of-care testing of NADH in real human serum - Ji, Dongqing; Ying, Zi; Zhang, Yuan; Chen, Wei; Janyasupab, Metini; Gao, Xinghua; Feng, Lingyan; Wen, Weijia (My University, 2020)
Dihydronicotinamide adenine dinucleotide (NADH) is an important enzyme in all living cells, which is found to be abnormally expressed in cancer cells. Since it is redox-active, an electrochemical detection method would be suitable for monitoring its concentration in biological fluids. Here we present a strategy for specific determination of NADH in real human serum by using RhIr@MoS2 nanohybrids based microsensor. To implement the protocol, RhIr nanocrysrals are in-situ grown onto MoS2 interlayers forming a nanohybrid structure (RhIr@MoS2). After being locally deposited on an electrochemical microsensor, it could be used for the analysis of NADH. The developed RhIr@MoS2 nanohybrids based microsensor possesses the ability for analyzing NADH at the applied potential of 0.07 V (much lower than most reported values). The detection limit is evaluated as low as 1 nmol/L even in bovine serum albumin (BSA) media. In addition, the sampling analysis of human serum from cancer patients and health controls shows that the microsensor displays good diagnostic sensitivity and specificity, illustrating that this developed detection technique is a relatively accurate method for measuring NADH in biological fluids. The proposed electrochemical microsensor assay also owns the benefits of convenience, disposable and easy processing, which make it a great possibility for future point-of-care cancer diagnosis.
Keywords: Cancer diagnosis; Electrochemical microsensor; MoS2; Nanohybrid; Point-of-care (POC) test